Studierende und NGOs gegen Soldaten - Ioannis Brigkos (Österreichische Zeitschrift für Geschichtswissenschaften)
This paper attempts to provide a new explanation of Austria’s diplomatic modus operandi in relation to Greece’s diplomatic capacity under the rule of the military dictatorship, from 1967 to 1974. Within the premises of the New Diplomatic History, it will be shown that during this period, even though Austria often exercised its realpolitik and covertly supported the Greek Junta or invested in it financially, certain circumstances burdened the interstate relations between Vienna and Athens, including the anti-dictatorial efforts of Greek students in Austria and those of the president of the Socialist International, Bruno Pittermann. These unofficial diplomatic agents had a major impact on Greek-Austrian relations, creating tension between the two countries without breaking them completely.